2 - Academic Programme Leadership in African Higher Education: A Phenomenological Reflection - Shawa, Lester Brian (Journal of Higher Education in Africa, 2022)
Given a dearth of literature on the role of middle-level academics in African higher education, this article contributes to the understanding of the roles played by this cadre. In this article, I draw on my lived experiences of leadership as an academic programme coordinator in higher education studies located at a higher education unit at a South African university. I pose two phenomenological questions: 1) how is it to be an academic programme leader, from my lived experiences of leadership at a South African university? and 2) what do my lived experiences of academic programme leadership reveal about programme leadership at a South African university? To answer these questions, I utilised a personal phenomenological reflection by drawing on concepts of lifeworld and being. The results showed that academic programme leadership was demanding and required paying attention to systemic contexts of universities as well as developing skills such as decision-making, curriculum development and pedagogical leading, and communication. These findings imply a need for careful planning of university structures, such as the locus of higher education units and their operations, a clearer definition of the role of academic programme leaders/coordinators and capacity building for academic programme leaders in South African universities.